relA Inactivation Converts Sulfonamides Into Bactericidal Compounds - Si, Lizhen; Gu, Jing; Wen, Mi; Wang, Ruiqi; Fleming, Joy; Li, Jinyue; Xu, Jintian; Bi, Lijun; Deng, Jiaoyu (Frontiers in Microbiology, 2021)
Folates are required for the de novo biosynthesis of purines, thymine, methionine, glycine and pantothenic acid, key metabolites that bacterial cells cannot survive without. Sulfonamides, which inhibit bacterial folate biosynthesis and are generally considered as bacteriostats, have been extensively used as broad-spectrum antimicrobials for decades. Here we show that, deleting relA in Escherichia coli and other bacterial species converted sulfamethoxazole from a bacteriostat into a bactericide. Not as previously assumed, the bactericidal effect of SMX was not caused by thymine deficiency. When E. coli ∆relA was treated with SMX, reactive oxygen species and ferrous ion accumulated inside the bacterial cells, which caused extensive DNA double-strand breaks without the involvement of incomplete base excision repair. In addition, sulfamethoxazole showed bactericidal effect against E. coli O157 ∆relA in mice, suggesting the possibility of designing new potentiators for sulfonamides targeting RelA. Thus, our study uncovered the previously unknown bactericidal effects of sulfonamides, which advances our understanding of their mechanisms of action, and will facilitate the designing of new potentiators for them.